2020
DOI: 10.1002/app.50209
|View full text |Cite
|
Sign up to set email alerts
|

The cavitation development of poly(4‐methyl‐1‐pentene) casting films studied by in situ small angle X‐ray scattering

Abstract: In this paper, the on‐line small angle X‐ray scattering/wide‐angle X‐ray scattering (SAXS/WAXS) characterization method was adopted to study the morphology evolution of poly(4‐methyl‐1‐pentene) casting films during stretching. In this process, the lamellae structure was destroyed. And “bridge structure” was generated in the amorphous region. The scattering pattern changed obviously before and after cavities orientation. Stretching temperature and stretching speed mattered for the size of micropores. Low temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…For the P4MP1 precursor film, the optimum annealing temperature and time were 205°C and 20 min, and the best cold and hot stretching temperatures were 70 and 180°C 23 . In the later work by Yin et al, 24–26 P4MP1 precursor film with different draw ratios was obtained and the optimum annealing parameters and stretching parameters were discussed. It was found that the crystallinity of the precursor film declines with increasing draw ratios.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the P4MP1 precursor film, the optimum annealing temperature and time were 205°C and 20 min, and the best cold and hot stretching temperatures were 70 and 180°C 23 . In the later work by Yin et al, 24–26 P4MP1 precursor film with different draw ratios was obtained and the optimum annealing parameters and stretching parameters were discussed. It was found that the crystallinity of the precursor film declines with increasing draw ratios.…”
Section: Introductionmentioning
confidence: 99%
“…During extrusion, a larger molecular weight, higher extrusion speed, and a larger quench height promote the formation of planar stacked lamellar texture and higher main-chain crystalline orientation factor. 21 For the P4MP1 precursor film, the optimum annealing temperature and time were 205 C and 20 min, and the best cold and hot stretching temperatures were 70 and 180 C. 23 In the later work by Yin et al, [24][25][26] P4MP1 precursor film with different draw ratios was obtained and the optimum annealing parameters and stretching parameters were discussed. It was found that the crystallinity of the precursor film declines with increasing draw ratios.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations